Basic research on an electric fixed-route bus system with green fast charging at every bus stop using a simulator - Takeshi KAWASHIMA (The Japan Society of Mechanical Engineers, 2017)
In a sustainable city, public transportation is prohibited from emitting greenhouse gases. A vehicle running on electric power generated from a green energy source does not emit carbon dioxide (a major greenhouse gas) and is thus optimal for reducing greenhouse gas emissions. To pursue this goal, we propose a public transport system consisting of electric buses that are quickly charged at every bus stop, using electric power generated from green energy sources. Such a system resolves the problem of low mileage per charge for heavy batteries. This system would also be able to effectively use low density and widely available solar energy to generate power at bus stops, which are widely distributed throughout a city. In this paper, an electric bus system that is rapidly charged at every bus stop, using electric power generated from green energy sources is introduced first. Next, the simple full-size electric bus simulator is constructed by extrapolating the parameters obtained from the single-passenger electric vehicle. Then, the simulations in some characteristic cases are performed, and the results are examined, especially the change of the state of charge (SOC) of the battery mounted on the bus, the energy charging to the bus at the bus stop and the travel time including the stoppages of 20 s at each bus stop. Last, the storage equipment capacity of the full-scale electric bus and the specifications of the bus stop, in particular the capacity of the solar modules, are estimated using the constructed simulator.